Factors Associated with the Utilization of Queue Services through the National Health Insurance Mobile Application - Aliffia Putri Saharani; Sunandar Said; Khaeriyah Adri; Devy Febrianti (Jurnal Keperawatan Profesional (KEPO), 2026)
Mobile National Health Insurance (Mobile NHI) is an application that facilitates users in registering, updating, and accessing membership data, obtaining services from primary and referral health facilities, and submitting feedback. This study aimed to analyze the factors associated with the utilization of queue services through the application in the working area of Rappang Public Health Center. This research employed a quantitative method with a cross-sectional approach. The study population consisted of 14,829 visits of National Health Insurance participants, with a sample of 99 subjects determined using the Slovin formula and simple random sampling technique. Data were collected through observation, documentation, and questionnaires that had been tested for validity and reliability. Data analysis was conducted using univariate and bivariate analysis with the Chi-Square test at a significance level of p < 0.05. The results showed that digital literacy, socialization, education level, and age were significantly associated with the utilization of queue services through the Mobile JKN application. It was concluded that the utilization of this service was still not optimal due to limited technological understanding and insufficient dissemination of information. The implications of this study highlighted the need to improve digital literacy, enhance interactive socialization strategies, and develop a more user-friendly application system to optimize the use of digital health services.